Forced ventilation and evaporative cooling of waiting and milking areas and its influence on the physiological and production responses of crossbred Holstein × Zebu cows - Amaral, R.S. (2011)
The main objective of this work was to evaluate the effect of forced ventilation and evaporative cooling on the physiological and production responses of dairy cows Holstein × Zebu. Experiments were conducted with 32 crossbred cows (Holstein × Zebu) in the same lactation phase, mean daily production of 17 kg and mean body weight of 550 kg. Four different treatments were randomly assigned to groups with eight cows each. The treatments were: Evaporative cooling in the waiting room + forced ventilation with Evaporative cooling in the milking room (NW+VNM), Evaporative cooling in the waiting room (NW), forced ventilation with Evaporative cooling in the milking room (VNM) and a control treatment without forced ventilation and evaporative cooling (CON). Experimental work was realised in a commercial farm located in the interior of Bahia State, Brazil, during 45 days in January and February. Climatic data were measured using a meteorological station. Temperature Humidity Index (THI) and Wet Bulb Globe Temperature (WBGT) were calculated. In order to study animal responses milk production, udder temperature, heart rate, respiratory rate, temperature of white and black spots and rectal temperature were measured. It was observed that the cows under VNM treatment presented higher milk production and lower udder temperature, heart rate, respiratory rate, temperature of white and black spots. No significant differences occurred in the rectal temperature. Results showed that forced ventilation and evaporative cooling positively influenced environmental conditions showing the importance of evaporative cooling for dairy cows.